Imaging outcomes for trials of remyelination in multiple sclerosis. Issue 12 (25th April 2014) - Mallik, Shahrukh; Samson, Rebecca S; Wheeler-Kingshott, Claudia A M; Miller, David H
Abstract : Trials of potential neuroreparative agents are becoming more important in the spectrum of multiple sclerosis research. Appropriate imaging outcomes are required that are feasible from a time and practicality point of view, as well as being sensitive and specific to myelin, while also being reproducible and clinically meaningful. Conventional MRI sequences have limited specificity for myelination. We evaluate the imaging modalities which are potentially more specific to myelin content in vivo, such as magnetisation transfer ratio (MTR), restricted proton fraction f (from quantitative magnetisation transfer measurements), myelin water fraction and diffusion tensor imaging (DTI) metrics, in addition to positron emission tomography (PET) imaging. Although most imaging applications to date have focused on the brain, we also consider measures with the potential to detect remyelination in the spinal cord and in the optic nerve. At present, MTR and DTI measures probably offer the most realistic and feasible outcome measures for such trials, especially in the brain. However, no one measure currently demonstrates sufficiently high sensitivity or specificity to myelin, or correlation with clinical features, and it should be useful to employ more than one outcome to maximise understanding and interpretation of findings with these sequences. PET may be less feasible for current and near-future trials, but is a promising technique because of its specificity. In the optic nerve, visual evoked potentials can indicate demyelination and should be correlated with an imaging outcome (such as optic nerve MTR), as well as clinical measures.